Reimagining Science Education in the Anthropocene, Volume 2 - Tolbert, Sara; Wallace, Maria F.G; Higgins, Marc; Bazzul, Jesse (Palgrave Studies in Education and the Environment, 2024)
This volume, a follow up to Reimagining Science Education in the Anthropocene (2021), continues a transdisciplinary conversation around reconceptualizing science education in the era of the Anthropocene. Drawing educators from many walks of life and areas of practice together in a creative work that helps reorient science education toward the problems and peculiarities associated with this contemporary geologic time. This work continues the mission of transforming the ways communities inherit science and technology education: its knowledges, practices, policies, and ways-of-living-with-Nature. Our understanding of the Anthropocene is necessarily open and pluralistic, as different beings on our planet experience this time of crisis in different ways. This second volume continues to nurture productive relationships between science education and fields such as science studies, environmental studies, philosophy, the natural sciences, Indigenous studies, and critical theory in orderto provoke a science education that actively seeks to remake our shared ecological and social spaces in the coming decades and centuries. This is an open access book.